2023
DOI: 10.3390/plants12142606
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Induces Heat and Salinity Tolerance in Wheat by Increasing Antioxidant Activities, Photosynthetic Activity, Nutrient Homeostasis, and Osmo-Protectant Synthesis

Ansa Aouz,
Imran Khan,
Muhammad Bilal Chattha
et al.

Abstract: Modern agriculture is facing the challenges of salinity and heat stresses, which pose a serious threat to crop productivity and global food security. Thus, it is necessary to develop the appropriate measures to minimize the impacts of these serious stresses on field crops. Silicon (Si) is the second most abundant element on earth and has been recognized as an important substance to mitigate the adverse effects of abiotic stresses. Thus, the present study determined the role of Si in mitigating adverse impacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 89 publications
3
9
0
Order By: Relevance
“…Lead stress induces phytotoxicity in leaves by degrading chlorophyll contents, and it also damages the photosynthetic apparatus, therefore leading to a reduction in chlorophyll synthesis . Salinity stress also reduced the synthesis of photosynthetic pigments, which could be attributed to increased ROS production (Table ) that damages the photosynthetic apparatus and degrades chlorophyll, resulting in a reduction in chlorophyll synthesis. , The exogenous supply of SWE improved the synthesis of photosynthetic pigments under both stresses, which is consistent with the findings of Tahira et al They found that the application of allelochemicals improves chlorophyll synthesis by reducing ROS production and decreasing the activity of chlorophyll degrading enzymes.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Lead stress induces phytotoxicity in leaves by degrading chlorophyll contents, and it also damages the photosynthetic apparatus, therefore leading to a reduction in chlorophyll synthesis . Salinity stress also reduced the synthesis of photosynthetic pigments, which could be attributed to increased ROS production (Table ) that damages the photosynthetic apparatus and degrades chlorophyll, resulting in a reduction in chlorophyll synthesis. , The exogenous supply of SWE improved the synthesis of photosynthetic pigments under both stresses, which is consistent with the findings of Tahira et al They found that the application of allelochemicals improves chlorophyll synthesis by reducing ROS production and decreasing the activity of chlorophyll degrading enzymes.…”
Section: Discussionsupporting
confidence: 87%
“…This reduction in growth was linked with increased EL, MDA, and H 2 O 2 production and disturbed nutrient homeostasis and antioxidant activities (Figures and ). Lead is a serious toxic that disturbs the soil microbial activity and plant functioning, resulting in a reduction in plant growth. , Salinity stress also induced ionic toxicity and increased ROS production (Table ), which caused a marked reduction by decreasing nutrient and water uptake . The foliar application of SWE appreciably improved the root and shoot growth of maize plants growing under Pb and salinity stress (Figures and ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This study reported that contents of chlorophyll a+b in L. chinensis was significantly decreased under salt-alkali stress. At the same time inoculated AM fungus inoculation significantly increased the synthesis of both chlorophyll contents possibly by increasing the uptake of important nutrients (iron and magnesium) that are considered to play a fundamental role in chlorophyll synthesis (Cao et al, 2021;Aouz et al, 2023;Khan et al, 2023b). This study further showed that under saline-alkali stress, gas exchange parameters (Pn, Gs, Tr) and chlorophyll fluorescence parameters (Fv/Fm, ΦPSⅡ, qP), were significantly decreased.…”
Section: Discussion Discussion Discussionsupporting
confidence: 51%